MICROBIAL CORROSION IN OIL INDUSTRY: A PRELIMINARY SURVEY OF THE PROBLEM - NOEGROHO HADI HS (Scientific Contributions Oil and Gas, 1982)
In 1977 Warren Spring Laboratory was authorised by the Engineering Materials Require ments Board of the Department of Industry to carry out a limited survey on the extent and magnitude of microbial corrosion in British Industry. The need for the survey arose because, despite all the microbial corrosion work which has been carried out in the past and the protection techniques which have been developed, microbial corrosion incidents con- tinue to occur, often causing considerable financial loss to industry. A questionnaire which would enable as much information as possible on microbial corrosion to be obtained from a wide variety of firms and organisations conceined in the manufacture and use of metal equipment. Since microbial corrosion has been most com- monly encountered as a problem with buried ferrous metals, considerable work has been done to develop techniques for assessing soil aggressiveness, Several of the survey questions were therefore directed to determine whether the recommended techniques were being applied, how effective these techniques were and of further experimental work was required. The economics of microbial corrosion protection were another area for which infor- mation was sought since the ultimate aim of a soil aggressiveness assessment is to enable the degree of protection given to a buried structure to be directly related to the measured aggressiveness, Thus unnecessary protection would be avoided.